Isolation and Characterization of Lactic Acid Bacteria (Lactobacillus sp) from Sauerkraut with the addition of Cayenne Pepper - Resti Fevria; Indra Hartanto (Bioscience, 2019)
Abstract. Sauerkraut is cabbage that is produced from natural fermentation by bacteria in the presence of 2.5 percent salt. Salt additions limits the activity of gram –negative bacteria, while the growth of lactic acid bacteria will increase. Chili is a vegetable of the genus Capsicum which has high economic value and also contains various compounds that are useful for human health. One method to get good quality cayenne is fermentation. Fermentation is part of biotechnology that uses microorganisms as the main actors in a process. One of the microbes that determines the success of fermentation is lactic acid bacteria.                The purpose of this study is isolate LAB from Sauerkraut with the additional cayenne pepper the type of LAB produced microscopically. Research methods, the ingredients used are cabbage and cayenne  fermentation (sauerkraut with the additional cayenne pepper), MRSa, 0,9% NaCl, crystal violet paint from biological laboratories UNP. Isolation LAB from Sauerkraut done in with fermentation Sauerkraut and then plant the sauerkraut into the MRSa medium with streak plate methods. The isolates obtained were identified microscopically using a microscope with gram staining method.                From the research that has been done, the following result are obtained : Sauerkraut with additional cayenne pepper direcly into MRSa medium and gram staining, there were 12 colonies of gram positive bacteria with bacil cell form, and negative catalase test.  We can identify this colonies as Lactobacillius sp.